2005
DOI: 10.5688/aj690466
|View full text |Cite
|
Sign up to set email alerts
|

The Current State of Pharmacy Informatics Education in Professional Programs at US Colleges of Pharmacy

Abstract: Objectives. Pharmacy practice is changing in response to several clarion reports published by the Institute of Medicine (IOM) documenting preventable medication errors. This paper seeks to assess the current curricula of US colleges of pharmacy to determine the readiness of new pharmacist graduates to do the pharmacy informatics work necessary to implement a safer, more information-rich medication use system. Methods. Data were collected from course titles and descriptions published on the public Internet web … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 5 publications
2
27
0
Order By: Relevance
“…Partnerships between health sciences programs, however, can increase the likelihood for funding, share the expense burden, and optimize the use of faculty time. The formation of the Interschool Advisory Council was a tremendous advantage in the course development process and was consistent with published recommendations 3 for identifying curricular content in informatics. Although the IOM report suggests that interdisciplinary instruction should be prioritized, 1 university and college and school policies may lag in their support of these recommendations.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Partnerships between health sciences programs, however, can increase the likelihood for funding, share the expense burden, and optimize the use of faculty time. The formation of the Interschool Advisory Council was a tremendous advantage in the course development process and was consistent with published recommendations 3 for identifying curricular content in informatics. Although the IOM report suggests that interdisciplinary instruction should be prioritized, 1 university and college and school policies may lag in their support of these recommendations.…”
Section: Discussionmentioning
confidence: 65%
“…Indeed, a recent comprehensive review of pharmacy informatics education in professional programs at US colleges of pharmacy suggests that only a third of pharmacy programs offer any courses in pharmacy informatics and even fewer (16%) require this coursework. 3 Through a similar review process conducted within their institution, the authors identified a need for informatics training in several of the health professions programs, suggesting that an interdisciplinary course would not only be consistent with the IOM recommendations, but also be an efficient method of introducing these concepts. To accommodate the difference in academic schedules among students in the different health programs as well as to illustrate the concept of ''using technology to teach about technology,'' it was determined that an online course would be the most …”
Section: Introductionmentioning
confidence: 99%
“…21 The use of computers to teach general or specialized practice skills varies by college. 22 Although ACPE recognizes the importance of technological training of students for practice, colleges of pharmacy have been slow to develop technological advancements in pharmacy instruction. The dearth of various forms of computer-aided learning in pharmacy curriculums leaves considerable room for development, deployment, and study.…”
Section: Discussionmentioning
confidence: 99%
“…Based on prior reviews [6][7][8] and additional evidence, 9 we propose an advanced curriculum outline intended as a guide to train enough pharmacy informaticists over the next decade to support the shift to a systems-supported practice for pharmacy taking place within a Learning Health System. This curriculum outline covers the necessary aspects of the domain of biomedical informatics to prepare enough pharmacy informaticists to participate effectively in four general categories of informatics work.…”
Section: Proposed Advanced Pharmacy Informatics Curriculum Outlinementioning
confidence: 99%